THE UTILIZATION CULTURAL RELEVANT ENGLISH TEACHING MATERlIAL TO HIGH SCHOOL STUDENTS IN PAPUA - Yohana Susana Yembise (Celt: A Journal of Culture, English Language Teaching & Literature, 2010)
The paper presents research findings on research project exploring the effect of culturally familiar material on students' academic achievement. It provides some related findings to the study. The research questions are (1) Is there an effect of the culturally familiar material on students' reading comprehension; (2) Is there an effect of culturally familiar material on students' mastery of vocabulary? The study involved two experimental and two control groups of 80 West Papuan highlander students aged 13-14 from multi-ethnic backgrounds. They werefluent speakers of L1, were not very fluent in Indonesian, and were considered academically weak. Both cohorts were pre-tested using cultural versus conventional reading and vocabulary tests before treatment. 85 hours of classroom presentation was given using culturally familiar material versus conventional material, finally subjects were post-tested. Exploratory Data Analysis and Repeated Measure ANOVA were applied and revealed that subjects using culturally familiar material made a significant improvement in their academic achievement when contrasted with subjects who received conventional material.